- Auditor’s Integrity: The Balance of Roles - Fibriani, Rudiana (Universitas 17 Agustus 1945 Surabaya, 2023)
Auditor integrity is very important to ensure audit quality. However, auditor integrity can be influenced by pressure from superiors such as role conflict, role ambiguity, and role overload. This study aims to examine the effect of the three role pressure factors on auditor integrity and performance. This quantitative research with a causality approach was conducted through Google Form by involving staff auditors who work for 52 KAPs in Surabaya. Then the primary data was analyzed using SmartPLS. The results show that role conflict and role ambiguity have a significant negative effect on auditor integrity, while role overload has a positive but insignificant effect. Auditor integrity significantly negatively mediates the effect of role conflict and role ambiguity on auditor performance, and significantly positively mediates the effect of role overload on auditor performance. This study concludes that role pressure can threaten auditor integrity, so steps need to be taken to reduce pressure so that auditors can maintain their integrity. Keywords: Role Conflict, Role Ambiguity, Role Overload, Auditor Integrity, Auditor Performance.